Axial load capacity and failure mechanism of flange and ring joints of process piping system. (March 2021) - Li, Gang; Wang, Wei; Duan, Xuanmeng; Dong, Baiping
Abstract: This paper investigates the capacity and failure mechanism of flange and ring joints of a process piping system under axial load using integrated experimental study and finite element analysis (FEA). The experimental results show that the stiffness and strength of the joints are lower than those of the pipes connected by the joints. The flange joint has greater initial stiffness and ultimate capacity than the ring joint, while has smaller ultimate deformation capacity than the ring joint. Under axial tensile load, the flange joint fails by thread shear failure, while the ring joint fails by the pullout of the convex ring from the free flange. Finite element models of the joints are created using the software program ABAQUS for FEA to further understand the experimental results and evaluate the capacity and failure mechanism of the joints. Finally, a simplified method is proposed to calculate the tensile stiffness and capacity of the joints, and design requirements are advised to keep the joints in good sealing performance under tensile loads Graphical abstract: Unlabelled Image Highlights: Experimentally investigated and compared the load capacity and failure modes of the flange and ring joints. Created finite element models to enable comprehensive evaluation of the capacity and failure mechanism of the joints. Proposed a simplified method to calculate the stiffness and capacity of the joints for engineering design. Proposed specific design requirements to ensure the joints to have good sealing performance.